PERLINDUNGAN HUKUM MASYARAKAT TERHADAP PENYAKIT MENULAR AKIBAT BIOTERORISME - Anggraeni Endah Kusumaningrum (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2020)
Many Indonesian people do not understand and are aware of the infectious diseases caused by bioterrorism. Bioterrorism is an act of terrorism that uses biological weapons in the form of bacteria, viruses, toxins, and fungi. This terrorist act is carried out by utilizing a virus, an infectious germ that is used by terrorist organizations as a means of attack to cause damage and is very dangerous to human health and safety. This study uses a normative juridical approach method, and secondary data as primary data supported by primary data. The secondary data are in the form of primary, secondary and tertiary legal materials that are analyzed qualitatively. Based on the analysis, it was revealed that through Law Number 36 Year 2009 it has regulated the rights and obligations of the community related to the right to health for themselves, however if related to the rights and obligations resulting from threats arising from infectious diseases due to bioterrorism this law has not yet regulated specifically, so that people still stutter associated with the threat of bioterrorism that can threaten their health and safety. Therefore, implementing regulations are still needed related to the threat of bioterrorism to provide protection and legal certainty to the community.